Leveraging Ansible for Middleware Scalability in Financial Services: A Technical Deep Dive - Pramod Muppala Kumar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The evolution of financial services infrastructure has created unprecedented challenges in managing middleware systems, particularly as institutions balance legacy systems with modern digital demands. This technical article examines how Ansible’s automation capabilities can transform middleware management in financial institutions. It explores the complex challenges facing financial organizations, including system integration, security compliance, and operational efficiency. The article analyzes Ansible’s architecture and its suitability for financial services, particularly its agentless design and robust security features. It encompasses automated provisioning, configuration management, and security automation frameworks. The article demonstrates how Infrastructure as Code principles when implemented through Ansible, enable consistent deployments while maintaining security and compliance. It also addresses implementation best practices, including process standardization, team structure, and quality assurance measures. Through a comprehensive examination of these aspects, the article provides insights into how financial institutions can leverage Ansible to achieve scalable, secure, and efficient middleware management while meeting regulatory requirements and maintaining operational excellence.